The impact of Extended Public Works Programmes on poverty alleviation in the Bushbuckridge Municipality in the Mpumalanga Province - Mothapo, Matšatši Frederick (My University, 2011)
The study focused on the existence of Extended Public Works Projects (EPWP) and beneficiation in the village of Croquetlawn and Tsemamarhumbu village of Mkhuhlu in the Bushbuckridge Municipality. Many rural households live in situations of high unemployment and abject poverty, especially in the rural neighbourhoods of South Africa. The introduction of labour intensive projects of government in infrastructural development, under the auspices of the Department of Public Works, has brought a great relief in redressing unemployment and poverty in the country. While the provision of these short-term based jobs is life-saving, the question is whether or not these projects (EPWP) will provide a sustainable solution to unemployment and poverty with the skills and information they provide to the employees. The methodology used in this study was both qualitative and quantitative in nature. A small sample size of 40 people was selected using purposive sampling, targeting mainly beneficiaries of EPWPs, Municipal officials, CBOs, traditional leaders (indunas) and Ward Councillors. It is worth pointing out that the study findings indicated the positive impact of the EPWPs on beneficiaries; even though challenges were still enormous. At the delivery or grassroots point, the institutional arrangement of the Programme is virtually weak and non-existent in most instances resulting in poor governance. It is recommended that during the programme design stage, institutional arrangements and mechanism must be improved by the involvement of community structures to enhance good governance. It is recommended that gender mainstreaming forms part of the project management and programme design. This implies that vulnerable people such as women and orphaned children are given a special status in the programme. The programme design should also in the main address human basic needs related to infrastructural projects. Labour intensive programmes can create a greater demand for local products and services than do high technology programmes which may heavily rely on imported technology and equipment.
Thesis (M.Dev.) -- University of Limpopo, 2011
Keywords: Poverty alleviation; Extended Public Works Programmes; Unemployment; Municipal services; Poverty -- South Africa -- Mpumalanga; Local economic development; Rural development; Rural poor -- Economic conditions